Clinical utility of complex assessment with evoked potentials in acute lymphoblastic leukemia survivors: comparison of various treatment protocols - Slawomir Kroczka; Konrad Stepien; Izabela Witek-Motyl; Kinga Kwiecinska; Eryk Kapusta; Agnieszka Biedron; Pawel Skorek; Szymon Skoczen (BMC Cancer, 2021)
Abstract Background One of the greatest success of pediatric hematology is a prominent improvement of survival in acute lymphoblastic leukemia (ALL). Therefore, special attention needs to be paid to long-term side effects of the treatment such as neurotoxicity. One of the few diagnostic methods that allow an objective assessment of sensory systems are evoked potentials (EP). Methods The analyzed group consisted of 167 ALL long-term survivors, aged 4.9–28.4 years, without auditory, visual and sensory deviations. Patients were treated with New York (NY, n = 35), previous modified Berlin-Frankfurt-Münster (pBFM, n = 47) and BFM95 (n = 85) protocols. In order to assess the impact of radiotherapy on recorded EP, a joint analysis of NY and pBFM groups was performed. The control group consisted of 35 patients, aged 6–17 years. The analyzed patients underwent a complex assessment with visual EP (VEP), somatosensory EP (SEP) and brainstem auditory EP (BAEP) in accordance with current standards. Results ALL treatment contributed to the shortening of wave I latency (1.59 vs 1.90, P = 0.003) and prolongation of I-III (2.23 vs 2.04, P = 0.004) and I-V (4.57 vs 4.24, P = 0.002) interwave latencies of BAEP. A significant effect was also noticed in P100 (106.32 vs 101.57, P < 0.001) and N135 (151.42 vs 138.22, P < 0.001) latencies of VEP and N18 amplitude (3.24 vs 4.70, P = 0.007) and P25 latency (21.32 vs 23.39, P < 0.001) of SEP. The distribution of abnormalities between protocols was similar in BAEP (NY - 68.6%, pBFM - 61.7%, BFM95–69.4%, P = 0.650), VEP (NY - 68.6%, pBFM - 42.5%, BFM95–58.3%, P = 0.053) and significantly different for SEP (NY - 62.9%, pBFM - 36.2%, BFM95–53.0%, P = 0.045). The harmful effect of radiotherapy was most clearly marked in numerous disturbances of SEP parameters. Conclusions The presented analysis indicates a high frequency of subclinical abnormalities in EP regardless of the analyzed protocol. To our knowledge current study is the largest and one of the most complex research examining the role of EP in ALL patients. The obtained results indicate the possibility of using a single, objective and non-invasive measurement of EP in ALL survivors in order to stratify the risk of developing sensory abnormalities in adulthood.